THE NEED FOR DENTAL TREATMENT IN PATIENTS WITH SENILE DEMENTIA - Oana Cristina Cretu; Marius Cocu; Elena Rodica Popescu (Romanian Journal of Medical and Dental Education)
This study examines the need for dental treatment in patients with senile dementia, focusing on the common oral health issues and challenges in managing dental care for this population. Due to cognitive decline, patients with senile dementia often struggle with maintaining oral hygiene, leading to conditions like tooth decay, periodontal disease, and infections. The study includes assessments of patients’ oral health status, interviews with caregivers and dental professionals, and an evaluation of barriers to effective treatment, such as communication difficulties and behavioral issues. Findings emphasize the importance of tailored dental care approaches and the role of caregiver involvement in improving oral health for dementia patients.